Pengaruh Tax Amnesty dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi yang Terdaftar di Kantor Pelayanan Pajak Pratama Kupang - Elizabeth Santje Suzana Prastiwi Rihi; Yohanes Demu; Minarni A. Dethan (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study was suppose to determine the influence of tax amnesty and tax sanctions on individual tax-payers compliance at KPP Pratama Kupang. This research type is quntitive research with incidental sampling as the sampling technique. The sample in this research are the 100 individual tax payers registered in KPP Pratama Kupang. The method of collecting data in this study is using a questionnaire. The research instrument is analyzed using validity and reliability tests. Data analysis technique used in this study are classical assumptions test and multiple linear regression analysis. The analytical tool used is the Statistical Package for the Social Sciences 26 (SPSS 26). The results of this study indicate that: tax amnesty and tax sanctions influence both partially and simltaneously on induvidual tax-payers compliance registered in KPP Pratama Kupang.